Left Lateral Sectionectomy of the Native Liver and Combined Living-Related Liver–Kidney Transplantation for Primary Hyperoxaluria Type 1. Issue 31 (August 2015) - Chen, Guo-Yong; Wei, Si-Dong; Zou, Zhong-Wu; Tang, Gao-Feng; Sun, Jian-Jun; Zhou, Shao-Tang; Marco, Biolato.
<x xml:space="preserve">Abstract</x> Abstract Primary hyperoxaluria type I (PH1), the most severe form of primary hyperoxalurias, is a liver disease of the metabolic defect in glyoxylate detoxification that can be corrected by liver transplantation. A 21-year-old man presented to our center after 4 months of regular hemodialysis for kidney failure caused by nephrolithiasis. A diagnosis of PH1 was confirmed by mutations of the AGXT gene. Left lateral sectionectomy of the native liver was performed; and auxiliary partial orthotopic liver transplantation (APOLT) and kidney transplantation were carried out synchronously using a living donor. After transplantation, the patient's plasma oxalate and creatinine levels substantially decreased and the patient recovered well with good dual grafts function. APOLT and kidney transplantation can compensate the liver deficient in liver enzyme production and aid the renal elimination of oxalate, thus serving as an effective treatment option for patients with PH1. In conclusion, left lateral sectionectomy of the native liver and combined living-related liver–kidney transplantation can be a surgical option for PH1.